The effect of water purification systems on fluoride content of drinking water - Prabhakar A; Raju O; Kurthukoti A; Vishwas T (Wolters Kluwer Medknow Publications, 2008)
Objective: The purpose of the present study was to determine the effect of different water purification systems on the fluoride content of drinking water and to compare the efficacy of these water purification systems in reducing the fluoride content. Materials and Methods: Five different water purification systems were tested in this study. They were reverse osmosis, distillation, activated carbon, Reviva ® , and candle filter. The water samples in the study were of two types, viz, borewell water and tap water, these being commonly used by the people of Davangere City, Karnataka. The samples were collected before and after purification, and fluoride analysis was done using fluoride ion-specific electrode. Results: The results showed that the systems based on reverse osmosis, viz, reverse osmosis system and Reviva ® showed maximum reduction in fluoride levels, the former proving to be more effective than the latter; followed by distillation and the activated carbon system, with the least reduction being brought about by candle filter. The amount of fluoride removed by the purification system varied between the system and from one source of water to the other. Interpretation and Conclusion: Considering the beneficial effects of fluoride on caries prevention; when drinking water is subjected to water purification systems that reduce fluoride significantly below the optimal level, fluoride supplementation may be necessary. The efficacy of systems based on reverse osmosis in reducing the fluoride content of water indicates their potential for use as defluoridation devices.